Lead cleavage sites in the core structure of group I intron-RNA. - Streicher, B (1993)
Self-splicing of group I introns requires divalent metal ions to promote catalysis as well as for the correct folding of the RNA. Lead cleavage has been used to probe the intron RNA for divalent metal ion binding sites. In the conserved core of the intron, only two sites of Pb2+ cleavage have been detected, which are located close to the substrate binding sites in the junction J8/7 and at the bulged nucleotide in the P7 stem. Both lead cleavages can be inhibited by high concentrations of Mg2+ and Mn2+ ions, suggesting that they displace Pb2+ ions from the binding sites. The RNA is protected from lead cleavage by 2'-deoxyGTP, a competitive inhibitor of splicing. The two major lead induced cleavages are both located in the conserved core of the intron and at phosphates, which had independently been demonstrated to interact with magnesium ions and to be essential for splicing. Thus, we suggest that the conditions required for lead cleavage occur mainly at those sites, where divalent ions bind that are functionally involved in catalysis. We propose lead cleavage analysis of functional RNA to be a useful tool for mapping functional magnesium ion binding sites.